Microstructure, phase morphology, eutectic coupled zone and hardness of Al–Co alloys - Silva, Cássio A.P.; Kakitani, Rafael; Canté, Manuel V.; Brito, Crystopher [UNESP]; Garcia, Amauri; Spinelli, José E.; Cheung, Noé (Elsevier, 2020)
This study examines the roles played by crystal growth rates (V) and cooling rates (Ṫ) on the microstructural evolutions of hypoeutectic (0.7 wt% Co), eutectic (1.0 wt% Co) and hypereutectic (1.5 wt% Co) Al–Co alloys. For this, these alloys have been directionally solidified by using a transient heat flow setup. It is shown that the microstructures of the 0.7 and 1.0 Co alloys are formed by α-Al matrices. In these alloys, a morphological reverse transition from α-Al matrix dendrites to cells is observed while a α-Al/ Al9Co2 eutectic mixture is also contained. In the Al- 1.5 wt% Co alloy, the prevalence of eutectic features occurs. Experimental growth laws relating cellular, dendritic and eutectic spacings to V and Ṫ are determined. Plots relating V and Ṫ to the alloys Co contents are proposed. The latter allow the range of coupled growth during transient solidification of Al–Co alloys to be examined. The hypereutectic alloy (1.5 wt% Co) demonstrates increase of about 41% in hardness as compared to the other examined alloys.
Keywords: Al-composite; Al–Co alloys; Microhardness; Microstructure; Solidification